DIGITALISASI DATA SKRINING KESEHATAN MASYARAKAT MELALUI APLIKASI PENCATATAN BERBASIS KOMPUTER - Wijaya Widiyanto, Wahyu; Sunandar, Ahmad (APTIRMIKI, 2025)
Recording the results of community health screening is still mostly carried out manually, which often leads to errors and hinders data analysis and reporting. This community service activity aims to introduce and implement a computer-based recording application to support the digitalization of health screening data. The methods used included community education, basic health screening such as measuring height and blood pressure, and recording the results into a simple application developed using data processing software. The results of the activity showed increased recording speed, easier data recap, and more accurate information processing compared to manual recording. The community also gained a better understanding of the importance of regular health screening and the benefits of using information technology. In conclusion, the implementation of a computer-based recording application can improve the effectiveness of health screening data management and strengthen the role of information technology in community health services.